The pharmacokinetics of enalapril in hospitalized patients with congestive heart failure. - Dickstein, K (1987)
The pharmacokinetics of the converting enzyme inhibitor, enalapril, were studied in an open, randomized, balanced crossover design in 12 hospitalized patients with stable, chronic congestive heart failure (CHF). Enalapril maleate is a prodrug requiring in vivo hepatic esterolysis to yield the active diacid inhibitor enalaprilat. CHF results in changes in regional blood flow that may affect the gastrointestinal absorption, hepatic hydrolysis and renal excretion of enalapril and enalaprilat. In order to evaluate the pharmacokinetics of enalapril in CHF, the following treatments were given: enalapril maleate 10 mg orally, enalapril maleate 5 mg intravenously and enalaprilat 5 mg intravenously. Each dose was followed by a 72 h period with frequent blood sampling and fractionated urine collection for the radioimmunoassay of enalaprilat, before and after sample hydrolysis. Mean absorption for the oral dose was 69%, hydrolysis 55%, bioavailability 38%, urinary recovery 77% and estimated first-pass effect 10%. The results were compared with available data in normal subjects. After oral administration of 10 mg enalapril maleate, the extent of absorption, the degree of hydrolysis and the bioavailability in CHF patients appear to be similar to those in normals with differences less than 10%. The rate of absorption and hydrolysis appear to be slightly slower in CHF. The serum concentrations of enalaprilat were consistently greater in CHF and maximal concentrations were reached at 6 h in CHF as compared to 4 h in normal subjects. We conclude that the presence of CHF does not appreciably alter the pharmacokinetic behaviour of enalapril. The observed differences may be associated with age as well as the disease state.